A Comparative Study on Effective Clinical Instruction: The Millennial Generationâ€™s Perspective - Villano, Dominga; Indonto, Maria Charito Laarni; Briones, Marifa; Molina, Roger (European Scientific Journal, ESJ, 2020)
Introduction: This study aimed to determine learnersâ€™ perceptions of the characteristics of an effective clinical instructor and the determining factors for that perception. Materials and Methods: This study used a quantitative-cross sectional design. The participants of this study were 100 nursing students obtained from convenience sampling. These students were enrolled in the College of Nursing of the University of Hail in the first semester of 2019-2020. Data was collected from January to April 2020. Results: The majority of students identified â€œskillfulâ€ as the most important characteristic (x=4.26; SD= 3.86), followed by â€œgood communicatorâ€ (x=4.15; SD=3.77), and â€œapproachableâ€ and â€œskillful,â€ both with means of 4.05(SD= 4.30). A significant difference was found in gender (t value-2.497; p<.0.014) but not year level (t value= 1.010; p> 0.315). Conversely, ANOVA results found no significant differences in age (f-value= 2.095; p>.05), marital status (f-value=0.393; p> 0.676), and the amount of exposure per week (fvalue= 2.894; p>0.060). Conclusion: Skillful emerged as the most important characteristic of an effective clinical instructor. Moreover, the female learners seemed to have a different requirement of an effective teacher (e.g. positive behavior). This information is imperative for school authorities to find ways to meet learnersâ€™ expectations. Meeting the needs and expectations of the learners can serve as a valuable indicator for the facilitatorâ€™s effectiveness.